Grimm. Season four [videorecording (DVD)] - Carpenter, Stephen (Screenplay author); Greenwalt, David; Kouf, Jim (Universal Studios Home Entertainment, 2015)
In the wake of Monroe and Rosalee's wedding, things have never been more chaotic. Nick, having lost his Grimm abilities, must dig deep and decide what type of person he wants to be. With Captain Renard in critical condition after being gravely injured and Juliette trying to come to grips with Nick's recent betrayal, the world of Grimm is spiraling out of control more than ever. Watch all 22 spine-chilling episodes.